Comovements in the Real Activity of Developed and Emerging Economies: A Test of Global versus Specific International Factors - Antoine A. Djogbenou (Queen's University, Department of Economics, 2017)
This paper proposes a statistical test for the decoupling of the comovements in the real activity of developed and emerging economies. Although globalization has shaped the world economy in recent decades, emerging economies such as China have experienced impressive growth compared to developed economies, suggesting a decoupling between developed and emerging business cycles. Using economy activity variables measured by the log differences of the gross domestic product and the industrial production of developed and emerging countries, we investigate whether the latter assertion can be supported by observed data. Based on a two-level factor model, we assume these activity variables can be decomposed into a global component, emerging or developed common component and idiosyncratic national shocks. Furthermore, we propose a statistic that tests the null hypothesis of a one-level specification, where it is irrelevant to distinguish between emerging and developed latent factors against the two-level alternative. This paper provides a theoretical justification and simulation evidence that documents the testing procedure. An application of the test to our panel of developed and emerging countries leads to strong statistical evidence against the null hypothesis of coupling developed and emerging activity factors. Using a sequential principal component method, we identity global, developed and emerging economy activity factors from a two-level factor model. We find that these factors are able to track major economic events since 1996.
Keywords: C12; C55; F44; O47; 330; latent factor; decoupling; emerging and developed countries; global economy activity; test statistic